Pengembangan dan Validasi Metode KLT-Densitometri untuk Analisis secara simultan Parasetamol, Asam Mefenamat dan Ibuprofen dalam Jamu “Pegel Linu” - Hayun Hayun; Mulia Ade Karina (Jurnal Sains Farmasi & Klinis, 2016)
Jamu is a traditional or herbal medicine that is widely used by Indonesian people for prevention, maintenance and treatment of diseases. Traditional medicines contain plants or extracted plant material, or combinations thereof. The adulteration practice violates the laws. However, the presence of undeclare synthetic chemical drugs in the herbal products are still often found, among others, analgesic and anti-inflammatory drugs. The purpose of this study is to obtain a validated, simpler and lower operational cost of TLC-densitometric method to analyze paracetamol, mefenamic acid and ibuprofen in herbal medicines in “pegel linu” herbal medicines. The samples were extracted with ethanol, then separated over silica gel GF254 TLC plate with mixture of chloroform-ethanol (8:1) as mobile phase and analyzed using TLC-densitometry. The method has a satisfactorily specificity and linearity, and met the precision and accuracy criteria at the concentration of 1500 ng/spot for paracetamol, 1250 ng/spot for mefenamic acid, and 2000 ng/spot for ibuprofen. The results of the determination of eight samples showed that four of them were positive containing paracetamol with the concentration of  337.12 - 505.55 mg/single dosage.